(untitled) (Proceeding of the International Conference on Arts and Humanities, 2019)
This paper suggests that the transformative nature of fairy tales is rooted in them serving as “mirrors” or reflectors of changes in the ideals held by the general populace, variance in norms or a change in acceptability of certain behaviors. It also seeks to observe the use of these stories as “tools” to encourage the acceptability of specific behaviors that deviate from norms previously held such as an increase in female agency, acceptability of homosexuality, and a defiance of the “damsel in distress” trope, or rather the “Prince as Savior” trope in contemporary times. It compares versions of popular fairy tales, with “Sleeping Beauty” as a key example, across media, both textual and audio visual. This paper attempts to identify the varying elements in these retellings across four broad timelines, categorized in this paper as (a) Pre-Grimm, (b) The Grimm Revolution (c) The “Disneyfication” and (d) Rejection/ Reconstruction and see how they correlate to changing ideals and views in the world they are incubated in and thus supposedly “reflect” or “mirror”.